Victims or criminals? Shifting interpretations of the over-representation of aborigines in the criminal justice system (2007)
In 1957, the Aboriginal Welfare Board (the authority in charge of the Aboriginal population in the State of New South Wales) questioned the soundness of one section of the Aboriginal Protection Act (APA, 1909-43) it administered. It therefore it launched a major survey in order to obtain the view on the question of all those «closely associated with aboriginal welfare and conduct», and in particular the members of the police. The Board did not just ask the police to state their opinion on the issue, but also to provide some figures about the Aboriginal population in their Patrol. The article analyses the construction of those figures, and it attempts to show how new interpretations emerged during the 1960s, especially through the rise of the political movement in favour of Aboriginal Rights.